2020
DOI: 10.1037/xlm0000729
|View full text |Cite
|
Sign up to set email alerts
|

Iconic gestures serve as manual cognates in hearing second language learners of a sign language: An ERP study.

Abstract: When learning a second spoken language, cognates, words overlapping in form and meaning with one's native language, help breaking into the language one wishes to acquire. But what happens when the to-be-acquired second language is a sign language? We tested whether hearing nonsigners rely on their gestural repertoire at first exposure to a sign language. Participants saw iconic signs with high and low overlap with the form of iconic gestures while electrophysiological brain activity was recorded. Upon first ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 43 publications
0
33
0
Order By: Relevance
“…Whether or not new M2L2 signers can try to capitalize on their gestural repertoire as a way to bootstrap learning a language in a visual modality has yet to be seen. Recent research has shown that hearing signers "generate expectations about the form of iconic signs never seen before based on their implicit knowledge of gestures" (Ortega et al 2019). It is still unclear whether ASL teachers could somehow leverage the knowledge of a gestural repertoire to teach constructed action or viewpoint constructions.…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not new M2L2 signers can try to capitalize on their gestural repertoire as a way to bootstrap learning a language in a visual modality has yet to be seen. Recent research has shown that hearing signers "generate expectations about the form of iconic signs never seen before based on their implicit knowledge of gestures" (Ortega et al 2019). It is still unclear whether ASL teachers could somehow leverage the knowledge of a gestural repertoire to teach constructed action or viewpoint constructions.…”
Section: Discussionmentioning
confidence: 99%
“…One important result coming out of this research is that L2 sign acquisition is affected by the iconicity of signs (e.g., Lieberth & Gamble, 1991; Campbell, Martin & White, 1992; Morett, 2015; Ortega, Özyürek & Peeters, 2019). Iconicity is a pervasive feature of many sign languages and is most often defined as the extent to which a sign resembles its meaning.…”
Section: Introductionmentioning
confidence: 97%
“…Such effects of gesture knowledge on the perception of sign meaning might be comparable to transfer effects that occur from L1 to L2 (e.g., MacWhinney, 1992). In fact, Ortega et al (2019) suggest that these iconic gestures function as “manual cognates” for hearing L2 learners of a sign language.…”
Section: Introductionmentioning
confidence: 99%
“…We chose to use English pseudowords because we were concerned that participants would focus attention on unfamiliar features and this would either disrupt normal word learning processes (e.g., rehearsal) or would allow individuals to use unfamiliar features as cues (e.g., a word produced with a click would be distinguished from all others). We did not, however, have this same concern with sign stimuli because, to the non-signer, all sign features should be relatively unfamiliar except in the case of iconic signs (Ortega & Morgan, 2015;Ortega, Ozyurek, & Peeters, 2019), which we attempted to avoid. While this potential confound is a valid concern, we note that we did use Turkish in one of our word learning tasks and it showed similar relationships as our other word learning tasks.…”
Section: Limitationsmentioning
confidence: 99%